2014
DOI: 10.1007/s10456-013-9413-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting VEGFR1 on endothelial progenitors modulates their differentiation potential

Abstract: PlGF plasma levels were found increased in cardiovascular patients. Disrupting PlGF/VEGFR1 pathway could modulate ECFC-induced tubulogenesis, the cell type responsible for newly formed vessels in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Several of the VEGFR1 functions that have been identified are in non-ECs (33,34,35,36,37,38) , and endothelial specific VEGFR1 functions remain uncertain. Our experimental data showed that VEGF 165 b-inhibition induces VEGFR1-activation not VEGFR2 or its downstream signaling in Balb/c ischemic muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the VEGFR1 functions that have been identified are in non-ECs (33,34,35,36,37,38) , and endothelial specific VEGFR1 functions remain uncertain. Our experimental data showed that VEGF 165 b-inhibition induces VEGFR1-activation not VEGFR2 or its downstream signaling in Balb/c ischemic muscle.…”
Section: Discussionmentioning
confidence: 99%
“…PlGF also binds to the neuropilin-1/VEGF165 receptor and stimulates angiogenesis [14]. Since its discovery in 1991 [15], PlGF has been associated with a number of disease states [16] including ischaemia [17], cardiovascular disease [18], cancer [19], arthritis [20] and preeclampsia [21]. Recent reports have revealed that there is increased secretion of PlGF from ECFCs isolated from end-stage renal failure patients [22] while in-vitro exposure to PlGF can enhance tubulogenic function in ECFCs [18].…”
Section: Introductionmentioning
confidence: 99%
“…The medium from Cell Applications is a defined medium containing a combination of EGF, FGF2 and VEGF. Specifically, VEGF promotes outgrowth of endothelial cell colonies from circulating endothelial progenitor cells (d’Audigier et al 2014) and thus, may be important for the attachment of single cells and the initiation of proliferation.…”
Section: Discussionmentioning
confidence: 99%